COVID-19 pandemic: An increase in Brazilian deforestation - Maciel, Harine Matos; Maciel, Wlisses Matos; Gomes, Maria Antunizia; Damasceno, Nagilane Parente (Seven Editora, 2023)
The objective of this research was to verify the increase in Brazilian deforestation rates during the Covid-19 pandemic. The research used was the bibliographic and the data used were of secondary origin obtained on the website of the National Institute for Space Research and the System for Estimating Greenhouse Gas Emissions of the Climate Observatory. The results showed that the rate of deforestation in the Legal Amazon increased by 35% due to the decrease in inspection and the relaxation of environmental legislation supported by the Federal Government. It was expected that with the reduction in economic activity due to the social isolation necessary to combat the Covid-19 pandemic, there would be a reduction in deforestation, but illegal deforestation activities continued with more intensity. Public power must assume the main role in combating deforestation actions since the preservation of natural environments is essential for the survival of human beings. DOI:https://doi.org/10.56238/emerrelcovid19-056